On the Accuracy of In Vivo Ethanol and Acetaldehyde Monitoring, a Key Tile in the Puzzle of Acetaldehyde as a Neuroactive Agent - Enrico, Paolo; Diana, Marco (Frontiers in Behavioral Neuroscience, 2017)
Over the last 20 years researchers have explored the postulated role of acetaldehyde (ACD) as a mediator of some of the actions of ethanol (EtOH) in the central nervous system (CNS). However, efforts have been hampered mainly by the difficulty of directly measuring in vivo EtOH and ACD levels in the CNS and thus, our knowledge is based on indirect evidences. Although technically challenging, the development of reliable methods for in vivo measurement of ACD and EtOH is of paramount importance to solve the “puzzle of acetaldehyde as a neuroactive agent”. In this short review we discuss the recent advances on brain EtOH pharmacokinetic and state-of-the-art available techniques that could be used for in vivo detect EtOH and ACD both non invasively (magnetic resonance spectroscopy), and invasively (microdialysis and biosensors). Among the different in vivo sampling techniques described, particular emphasis is paid to the field of enzyme-based amperometric biosensors. Biosensors have gained much attention in recent years for their ability to online monitor biological signals in vivo, and several micro- and nano-structured devices have been successfully used for in vivo studies. Owing to their high temporal and spatial resolution, biosensors could provide the adequate technology for studying in vivo EtOH pharmacokinetic.